PENGARUH PENAMBAHAN TEPUNG TAPIOKA TERHADAP KUALITAS KERUPUK DARI KULIT KAKAO (Theobroma L.) - Anita Dimu Lobo; Jublina Bakoil; Crisenia Julia Do Carmo (Politeknik Pertanian Negeri Kupang, 2023)
Cocoa crackers are dry food made from tapioca flour with additional ingredients of cocoa porridge, coriander, salt, Masako, and garlic, which result are solid and white in color. This study aims to determine the effect of adding tapioca flour on the quality of the crackers and the organoleptic quality of the cocoa crackers. This study used a completely randomized design ( CRD) method with 4 treatments repeated 3 times to obtain 12 experimental units. The variables observed were Texture, Color, and Taste. The data obtained were analyzed using variance (ANOVA) and continued with Duncan’s Multiple Range Test. The results of the analysis using variance (ANOVA) showed that treatments A, B, C, and D advertised the effect on Textur, Color, and Taste on cocoa crackers giving each treatment and effect ( A not real, B real, C nor real, D not real )Keyword: Cocoa froth, Cocoa meat, Cocoa crackers, Organoleptic.